Evaluation of an Authority Innovation-Decision: Brief Alcohol Intervention for Pregnant Women Receiving Women, Infants, and Children Services at Two Illinois Health Departments. (7th June 2014) - Moise, Imelda K.; Green, David; Toth, Janine; Mulhall, Peter F.
Abstract : Despite the availability of clinical tools and evidence-based screening recommendations, there has been little discussion regarding screening of prenatal alcohol exposure in community-based settings, including adoption and implementation. This study's aim is to evaluate and validate—through surveys and focus groups—obstacles and challenges that shape efficacious implementation of the BAI at two Illinois health departments. Results suggest that BAI implementation is facilitated by staff perceptions of its benefits, readiness to implement the intervention, and organizational support for it. Limitations of the management information system, ambiguous screening questions, and high case-loads present barriers to effective BAI implementation.